The COVID-19 variants: an overview - Pandey, Anuj K.; Mishra, Sidharth S.; wadgave, Yogesh; Mudgil, Nidhi; Gawande, Sonal; Dhange, Vijay B. (International Journal Of Community Medicine And Public Health, 2021)
The outbreak of novel coronavirus disease (COVID-19) was initially noticed in a seafood market in Wuhan city in Hubei Province of China in mid-December 2019 which has now spread to 223 countries/territories/areas worldwide. World Health Organization (WHO) under International Health Regulations (IHR) has declared this outbreak as a public health emergency of international concern (PHEIC) on 30th January 2020 subsequently declared a pandemic on 11th March 2020.